Comparison of Current Bacteriological Profile and Antibiotic Sensitivity Pattern in Tubotympanic Type of Chronic Suppurative Otitis Media between Adult and Pediatric Patients Presenting at Tertiary Care Hospital in Islamabad Pakistan - Ali, Maesum; Khurshied, Saleh; Hussain, Altaf; Ali, Muhammad; Khurshid, Ali (Indus Journal of Bioscience Research, 2025)
Background: CSOM, in its tubotympanic variety, continues to be one of the most common causes of a preventable cause of a hearing loss in developing countries, among both children and adults. Appreciating the prevailing bacteriological trends as well as antibiotic sensitivity patterns is crucial to the intervention as an increasing antimicrobial resistance loom over the horizon. Aim: To compare the present bacteriology and sensitivity of the antibiotics of adult and pediatric cases of tubotympanic type of CSOM attending a tertiary care hospital in Islamabad Pakistan. Methods: This comparative cross-sectional was carried out at PIMS Hospital Islamabad during a period of one year from the month of March 2024 to February 2025. Ninety patients with the diagnosis of tubotympanic CSOM were included, including 45 pediatric and 45 adult patients. Samples of Ears were collected and cultured through the standard microbiological approach. Isolates were subjected to test for their antibiotic susceptibility using Kirby-Bauer disc diffusion procedure as described in CLSI guidelines. Results: The most frequent isolate for the both groups was Pseudomonas aeruginosa and then Staphylococcus aureus. Nevertheless, P. Aeruginosa prevailed in the adults (48.9%) as compared to children (35.6%) whereas S. Aureus was found with a higher frequency in children (33.3%) as compared to adults (22.2%). Sensitivity pattern towards antibiotics dictated that P. aeruginosa had high sensitivity to ciprofloxacin and piperacillin-tazobactam in both populations, while resistance to ceftazidime was especially pronounced in the pediatric population. The S. aureus isolates were more sensitive to Vancomycin and linezolid and the methicillin resistance was more predominant in the adult cases. Conclusion: The study revealed clear differences of bacteriological profile and antibiotic sensitivity patterns between adult and pediatric patients with tubotympanic CSOM. The results underline the significance of the culture-directed therapy and the uninterrupted monitoring of the antimicrobial resistance to be able to prescribe antimicrobials bedside.